(untitled) (Journal of Science and Technology Research, 2023)
Air pollution is considered as the largest environmental health threat in the world. Last few years, it has also increased dramatically in different cities of Bangladesh. The air pollution of Dhaka city as well as other urban areas is very crucial for a sustainable environment. This research is mainly concentrated on studying a variety of air pollutants both qualitatively and quantitively during wintertime and checking the transboundary air pollution of Dhaka City. In the study area, air pollution was found to be at very dangerous levels. Even, air pollution has been found to be significantly higher in concentration during nighttime in Dhaka City. According to public perception and health physicians, air pollution causes many health problems such as eye irritation, headaches, COPD problem, skin cancer, hypertension, cardiovascular diseases, nausea, and asthma. Regular air quality monitoring can be effective for proper control measures of pollutants emissions that may protect the inhabitants from various illnesses. It can provide a guideline for the sustainable development of environment of city dwellers. J. of Sci. and Tech. Res. 4(1): 81-90, 2022